Når ’den gode medarbejder’ er maskulint konnoteret. Køn og positioner i lønsamtaler - Andersen, Pernille Tanggaard; Bloksgaard, Lotte (Kvinder, Køn & Forskning, 2006)
The article sheds light on how negotiations concerning gender take place in modern day work places where the discourse about equality of gender having been achieved is widely accepted. The article also unveils how the concept of equality of gender is redefined, e.g. in connection with the formation and utilisation of criteria concerning individual reward and salary negotiations. The article focuses on the impacts of gender neutrality by observing how employees and executives in 4 companies (Andersen & Bloksgaard 2004) talk about and use terms like ‘man’, ‘woman’ and ‘the good employee’. On this basis, organization, gender, work and work practices are analyzed.